CONSTIPATION IN CHILDREN CAUSES, PREVENTION, AND TREATMENT (International journal of medical sciences, 2026)
This article analyzes the problem of constipation, which is widely prevalent among children, including its main etiological factors, clinical manifestations, and types. The relationship between constipation and improper nutrition, dehydration, insufficient physical activity, psychological factors, and certain medical conditions is discussed. In addition, the complications of the disease, preventive measures, and treatment approaches are reviewed. The article emphasizes the importance of a balanced diet, adequate fluid intake, and regular physical activity in maintaining healthy bowel function in children.